A climatological overview of surface currents in the Arabian Gulf with special reference to the Exclusive Economic Zone of Qatar - Afnan Abdirashid Mussa (22504382) (2024)
This study derives the climatology of surface currents in the Arabian Gulf using the current velocities obtained from the Copernicus Marine Service (CMEMS) for the period 1993–2019. It reveals distinct temporal and spatial variability in the surface current speeds induced by the variability in surface winds, bathymetry and the changes in the lateral gradients in density. The mean speed of the Iranian Coastal Current (ICC) during summer reaches up to 0.33 m·s−1 along the coast of Iran, while the mean speed of Arabian Coastal Current (ACC) reaches up to 0.26 m·s−1 along the coast of Saudi Arabia. We found the occurrence of 2 major and 1 minor cyclonic eddies in the annual, seasonal and monthly climatology, while these eddies are more prevalent during summer. The major cyclonic eddy in the central Gulf develops in May and persists till November with varying patterns, and decays in December. The climatological mean current speeds are higher during summer compared to winter, due to the seasonal changes in thickness of the surface layer by the stratification/destratification processes. The highest mean current speeds along the coast of Qatar are found in June and the lowest in winter months. The highest annual, monthly and seasonal mean current speeds are observed along the north and northeast coast of Qatar, while the lowest are observed along the west coast and southeast coast of Qatar. Interannual variability in surface current speeds is evident, with notable links with the El Niño–Southern Oscillations (ENSO) and Indian Ocean Dipole (IOD). The annual mean current speeds show positive trends, of the order of 0.06–0.14 cm·s−1·year−1 in the offshore regions and 0.05–0.24 cm·s−1·year−1 in the nearshore regions, wherein the highest positive trend is observed off Ras Laffan and the lowest off Dukhan. Other Information Published in: International Journal of Climatology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/joc.8603